Application of a paraplegic gait orthosis in thoracolumbar spinal cord injury - Lang Shuai; Guo-hua Yu; Zhen Feng; Wan-song Wang; Wei-ming Sun; Lu Zhou; Yin Yan (Neural Regeneration Research, 2016)
Paraplegic gait orthosis has been shown to help paraplegic patients stand and walk, although this method cannot be individualized for patients with different spinal cord injuries and functional recovery of the lower extremities. There is, however, a great need to develop individualized paraplegic orthosis to improve overall quality of life for paraplegic patients. In the present study, 36 spinal cord (below T4) injury patients were equally and randomly divided into control and observation groups. The control group received systematic rehabilitation training, including maintenance of joint range of motion, residual muscle strength training, standing training, balance training, and functional electrical stimulation. The observation group received an individualized paraplegic locomotion brace and functional training according to the various spinal cord injury levels and muscle strength based on comprehensive systematic rehabilitation training. After 3 months of rehabilitation training, the observation group achieved therapeutic locomotion in 8 cases, family-based locomotion in 7 cases, and community-based locomotion in 3 cases. However, locomotion was not achieved in any of the control group patients. These findings suggest that individualized paraplegic braces significantly improve activity of daily living and locomotion in patients with thoracolumbar spinal cord injury.